A proteção integral da criança e do adolescente : enfrentamento ao abuso sexual a partir do estudo de caso do Projeto Luz - Pugliesi, Henrique de Carvalho (2023)
The present work aims to analyze, study and discuss about the engagement against child and adolescent sexual abuse in order to effectively implement the constitutional command of the integral protection of children and adolescents, from the perspective of the so-called "Projeto Luz". The study at hand was developed using the hypothetical-deductive method and is inserted in the research line of "Human Rights and Fundamental Rights" in the Stricto Sensu Postgraduate Program in Law at the Federal University of Mato Grosso. The research primarily focused on theoretical, especially bibliographic and empirical research. The study is divided into four chapters: the first chapter examines the normative evolution of child and adolescent protection; the second chapter explores the current legal stage of child and adolescent protection; the third chapter discusses the alarming number of crimes against children and adolescents currently in the country; and the fourth chapter analyzes the “Projeto Luz”, its main aspects and the results achieved. The case study of Projeto Luz, implemented in the Comarca of Nova Mutum, became a central point for the analysis of actions that proved to be effective for protection of children and adolescents victimized (or potentially victims) by sexual abuse. Ultimately, the need for urgent action to address the problem is concluded, either through the replication of the Projeto Luz in other municipalities or the implementation of similar projects that may use it as a model.